Determination of hygrothermal parameters of experimental and commercial bio-based insulation materials. (15th October 2016) - Palumbo, M.; Lacasta, A.M.; Holcroft, N.; Shea, A.; Walker, P.
Highlights: The hygrothermal properties of six bio-based materials is experimentally analysed. The materials show remarkable differences in their hygrothermal performance. The results are compared to numerical simulations, obtaining a good agreement. Different materials may have different impacts on the overall building performance. Abstract: The development and application of bio-based insulation materials can contribute to the minimization of the environmental impacts of buildings through reduction of embodied and in-use energy demand, in addition to many other major impacts such as resource depletion and waste generation. The hygrothermal performance of natural building materials has direct and indirect impacts on moderating indoor environmental conditions and can contribute to energy savings provided that such aspects are taken into account during the design and construction phases. This requires in-depth knowledge of the thermal and hygroscopic properties of the materials and their dependence on the moisture content. In this paper, the hygrothermal properties of six insulation materials is determined; four are commercially available materials while the other two are experimental materials based on crop by-products and natural binders. The influence of relative humidity on such properties is analysed. Moreover, the experimental Moisture Buffer Values are obtained for the six insulations, according to the protocol of the standard ISO 24353. Finally, a mass and heat coupled model is numerically solved to simulate this protocol for two of the materials, obtaining a good agreement with the experimental results.